Candidate gene association study suggests potential role of dopamine beta-hydroxylase in pain heterogeneity in sickle cell disease - Sadhu, Nilanjana; He, Ying; Yao, Yingwei; Wilkie, Diana J.; Molokie, Robert E.; Wang, Zaijie Jim (Frontiers in Genetics, 2023)
Pain is a lifelong companion of individuals with sickle cell disease (SCD) and has a severe impact on their quality of life. Both acute crisis pain and chronic non-crisis pain exhibit high variability between individuals, making it difficult to effectively manage sickle cell-related pain. We investigate the role of dopamine beta-hydroxylase (DBH) gene polymorphisms in variability of pain in SCD. DBH is a key enzyme in the catecholamine biosynthesis pathway that catalyzes the conversion of dopamine to norepinephrine, both of which are known mediators of pain and pain-related behaviors. Acute crisis pain-related utilization and non-crisis chronic pain scores of 131 African Americans with SCD were obtained. Association analyses revealed that the T allele of upstream variant rs1611115 and downstream variant rs129882 correlated with higher severity of chronic pain in an additive model. On the other hand, the A allele of missense variant rs5324 associated with lower risk of both acute crisis pain and chronic pain. Similarly, the C allele of intronic variant rs2797849 was associated with lower incidence of acute crisis pain in the additive model. In addition, tissue-specific eQTL revealed that the T allele of rs1611115 correlated with decreased expression of DBH in the frontal cortex and anterior cingulate cortex (GTEx), and decreased expression of DBH-AS1 in blood (eQTLGen). Bioinformatic approaches predicted that rs1611115 may be altering a transcription factor binding site, thereby, contributing to its potential effect. Taken together, findings from this study suggest that potential functional polymorphisms of DBH may modulate pain perception in SCD.